Challenges of Entrepreneurship Teaching in the Healthtech and Medtech Domains: Some Inputs for a New Approach - Koumpis, Adamantios; Finisterra do Paço, Arminda Maria; Beyan, Oya (International Journal of Online and Biomedical Engineering (iJOE), 2024)
The rapidly evolving landscapes of healthtech and medtech present unique challenges for entrepreneurship education, necessitating a specialized pedagogical approach. This paper explores pedagogical frameworks and the multifaceted barriers faced by educators in these domains. The cases presented emphasize the complexity and regulatory environment, the need for interdisciplinary knowledge, and the fast-paced technological advancements. Moreover, the convergence of medical knowledge with technological expertise demands a cross-disciplinary teaching strategy, complicating the traditional entrepreneurial education model. Additionally, the accelerated pace of technological change in healthtech and medtech outstrips conventional teaching methodologies, necessitating continuous curriculum updates and the incorporation of real-time industry developments. By addressing the current pedagogical challenges, entrepreneurship education in healthtech and medtech can more effectively equip students with the skills and knowledge needed to innovate and succeed in these highly specialized fields.